Navigating The Legal Landscape: Regulations And Frameworks For Ai In Dispute Resolution (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The evolution of technology has paved the way for transformative applications in various facets of human life. In the realm of conflict resolution, Artificial Intelligence (AI) emerges as a powerful ally, promising to enhance efficiency, accessibility, and fairness. This scientific article explores the nuanced integration of AI in dispute resolution, emphasizing the potential benefits, ethical considerations, and the crucial role of human oversight in creating a balanced and effective system.